Changing narratives: colonised peoples, criminology and social work - Chris Cunneen (International Journal for Crime, Justice and Social Democracy, 2014)
Abstract: There is growing recognition in criminology and social work of the importance of Indigenous knowledges and methodologies. Yet to date there have been limited attempts (particularly in criminology and criminal justice social work) to consider the theoretical and practice implications of Indigenous understandings and approaches to these disciplines. Both disciplines have also been slow to recognise the importance of understanding the way in which colonial effects are perpetuated through knowledge control, particularly in the operation of criminal justice systems. Our paper thus begins by examining the historical and institutional factors that have contributed to the continuing subjugation of Indigenous knowledges and methodologies. A discussion of the connections between the hegemony of Western science, the construction of race, and the colonial project follows. While herein Western and Indigenous approaches are conceptualised broadly, the dangers of over-simplifying these categories is also acknowledged. The paper proceeds by examining the distinctive character of each approach through a consideration of their ontological, epistemological, axiological, and methodological differences. Whilst acknowledging the considerable challenges which arise in any attempt to develop connections between these differing worldviews, a pathway forward for understanding both theoretically and methodologically the relationship between Western and Indigenous approaches is proposed